Proceedings of the 26th ACM Conference on Innovation and Technology in Computer Science Education v. 1 2021
DOI: 10.1145/3430665.3456370
|View full text |Cite
|
Sign up to set email alerts
|

Novices' Learning Barriers When Using Code Examples in Open-Ended Programming

Abstract: Open-ended programming increases students' motivation by allowing them to solve authentic problems and connect programming to their own interests. However, such open-ended projects are also challenging, as they often encourage students to explore new programming features and attempt tasks that they have not learned before. Code examples are effective learning materials for students and are well-suited to supporting open-ended programming. However, there is little work to understand how novices learn with examp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…During this process, programmers may directly copy a subset of an example code to their own code, or may reimplement a functionality by themselves after reading and learning an example [37]. Prior work has identified many barriers programmers encounter when integrating example code [36]. For example, Wang et al analyzed 44 novice programmers' example integration process and found that these programmers encounter barriers in understanding how to integrate an unfamiliar code block into their own context, mapping the functionality of a part of an example to their own code, and modifying the example to fit their own needs [36].…”
Section: A Code Reusementioning
confidence: 99%
See 3 more Smart Citations
“…During this process, programmers may directly copy a subset of an example code to their own code, or may reimplement a functionality by themselves after reading and learning an example [37]. Prior work has identified many barriers programmers encounter when integrating example code [36]. For example, Wang et al analyzed 44 novice programmers' example integration process and found that these programmers encounter barriers in understanding how to integrate an unfamiliar code block into their own context, mapping the functionality of a part of an example to their own code, and modifying the example to fit their own needs [36].…”
Section: A Code Reusementioning
confidence: 99%
“…Prior work has identified many barriers programmers encounter when integrating example code [36]. For example, Wang et al analyzed 44 novice programmers' example integration process and found that these programmers encounter barriers in understanding how to integrate an unfamiliar code block into their own context, mapping the functionality of a part of an example to their own code, and modifying the example to fit their own needs [36]. Wang et al also found that students prefer smaller code examples with few or no unfamiliar code blocks [36].…”
Section: A Code Reusementioning
confidence: 99%
See 2 more Smart Citations
“…The difficulties of programming education for novice learners have been confirmed through many studies [11][12][13]. The difficulty of the programming process is that when an error occurs, the cause is not known, so even if the problem is solved, the procedure is not correctly recognized.…”
Section: Introductionmentioning
confidence: 97%